Analisis Antrian Pendekatan Sistematis Untuk Mengurangi Waktu Tunggu di Klinik Kecantikan Rantauprapat - Hasibuan, Zamrotus Sholeha; Panjaitan, Nurmala; Ritonga, Laila Hasanah; Rambe, Anisah Rahma; Ritonga, Irmayanti (Journal of Computer Science and Information System(JCoInS), 2025)
Queues that occur at beauty clinics are often the main factor that causes inconvenience to customers, one of which is long waiting times. This study aims to analyze the queues at the Rantauprapat Beauty Clinic and propose a systematic approach to reduce waiting times. The method used in this study is queue analysis with a queuing theory approach, where customer arrival time and service time data are collected through direct observation at the clinic. The results of the analysis show an imbalance between the rate of customer arrivals and the available service capacity, which results in queue congestion. Therefore, it is recommended to implement a schedule-based queue management system or appointment system, add service personnel during peak hours, and improve the service system to speed up the process. By implementing these solutions, it is expected to reduce customer waiting time, increase operational efficiency, and provide a better experience for customers at the Rantauprapat Beauty Clinic.